What influences organisational evolution of modern sport: the case of skateboarding - Batuev, M.; Robinson, L. (Sport, Business and Management, 2018)
Purpose: The purpose of this paper is to investigate the processes that influence the evolution of a modern sport. It focusses on the case of international skateboarding: the sport that was recently included into the Olympic Games.